Structuring the water quality policy problem: Using Q methodology to explore discourses in the Brantas River basin - Houser, R. Schuyler; Pramana, Kharis Erasta Reza; Ertsen, Maurits Willem (Frontiers in Water, 2022)
Recognizing the interrelatedness of water use and conceptual value of IWRM, progressive water resource management systems are moving beyond hierarchical arrangements towards more integrated networks. Increasing calls for participation recognize the value of broadened perspectives that provide both technical expertise as well as social, cultural, and administrative knowledge. Moreover, the call for evidence-based policy of 00s has been tempered by recognition of the political nature of data and science. As such, water decision-makers striving to coproduce and employ shared knowledge must grapple with integrating inputs from diverse participant groups to characterize policy problems and identify effective and feasible solutions. Participatory mandates, coordination bodies, and collaborative networks have emerged to facilitate such integration, and their effective cooperation and alignment relies upon some degree of shared purpose, rather than command and control. But guidance is limited with respect to how to accomplish such integrative aims, including how to support discussions across sectors and silos of practice in order to foster better understanding regarding the problems a policy network collectively aims to address. Motivated by observations within the discourse on water quality in the Brantas River basin in Indonesia, this research explores alternative concepts and problem structures regarding river health via Q methodology. Q methodology, an approach that uses factor analysis to explore human subjectivity, is applied to explore conceptualizations of water quality and the structures of the “water quality problem” in the Brantas. The results show that different groups of perspectives emerge regarding the concept itself, as well as characterization of the current condition of the Brantas. Surprisingly, these variant perspectives do not follow oft-cited government-business-civil society divisions. Moreover, the emergent perspectives demonstrate which aspects of the policy problem are consistent and which are contested, suggesting several starting points for early collaboration and several areas that require further research and facilitated deliberation. The results also offer participants in the collaborative network greater appreciation of the various perspectives and definitions in use, within and across organizations, when discussing water quality.